2015
DOI: 10.1186/s13690-015-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with stunting and thinness among adolescent students in Northern Ethiopia: a comparison to World Health Organization standards

Abstract: BackgroundAdolescence is last chance for curbing the consequences of malnutrition and breaking the intergenerational cycle of malnutrition and poor health. This study aimed to assess the prevalence and the factors associated with stunting and thinness among in-school adolescents in northern Ethiopia using the 2006 World Health Organization (WHO) standards.MethodsIn-school adolescents (n = 348, 10–19 years old) were randomly selected to participate in this cross-sectional study. Anthropometric measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
116
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(153 citation statements)
references
References 41 publications
25
116
11
1
Order By: Relevance
“…We found only a few determinants that focused on community‐level factors. In general, rural residence, living in the hills versus lowlands, or living in slum areas were associated with undernutrition and status indexes . Furthermore, school type was associated with undernutrition, with adolescents attending public, instead of private schools, showing higher rates of undernutrition or poor nutrition .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…We found only a few determinants that focused on community‐level factors. In general, rural residence, living in the hills versus lowlands, or living in slum areas were associated with undernutrition and status indexes . Furthermore, school type was associated with undernutrition, with adolescents attending public, instead of private schools, showing higher rates of undernutrition or poor nutrition .…”
Section: Resultsmentioning
confidence: 91%
“…Mixed results were found regarding sex, with many studies reporting nonsignificant differences. Interestingly, studies reporting significant associations showed that boys were often worse off in terms of stunting and HAZ; underweight and WAZ; and thinness or WHZ . Only three studies in Ghana, Ethiopia, and Cambodia found that height or WAZ was lower for girls when compared with boys .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The health consequences of a prolonged Q2 state of malnutrition among children and adolescents include delayed their physical growth and impair motor and cognitive development, diminished cognitive performance [14,15], Several epidemiological studies have shown an association between physical developments in adolescent period with socio-economic status [16].…”
Section: Resultsmentioning
confidence: 99%